KEDUDUKAN HUKUM BADAN PERTANAHAN ACEH SEBAGAI BAGIAN DARI PERANGKAT DAERAH ACEH - Rahmad Jhowanda (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
Aceh is a province in the Republic of Indonesia, with special autonomy authority, such as authority in article 213, article 214, article 253 paragraph 1 of Law Number 11 Year 2006 concerning Aceh Government.The law has been followed up by Presidential Decree Number 23 of 2015 on the Transfer of Regional Offices of Aceh National Land Agency and Regency/ City Land Office to Aceh Land Agency and Land Office of Aceh Regency / City. To date the transfer of status has not been implemented. This research is analytical descriptive: normative juridical approach, primary data collection technique, data analysis method: qualitative analysis.The results of the research: Aceh Land Affairs Office, has not yet become Aceh Land Agency.No the formation of Qanun which regulates concretely about the authority of the Aceh Land Agency related to the transition, is also an important factor of the non-functioning of the Aceh Land Agency.The lack of clarity on the legal status of the Aceh Land Agency as part of Aceh's regional apparatus is seen in several articles at Perpres No. 23 of 2015, this is inconsistent with the Authority Theory in running the government, as well as the principles of local government affairs, among others: the principle of decentralization, the principle of deconcentration and the principle of co-administration. Keywords:  Aceh Land Agency, Presidential Regulation No. 23 Year 2015, Special Autonomy